1994
DOI: 10.1515/jpme.1994.22.2.113
|View full text |Cite
|
Sign up to set email alerts
|

t-PA activity in peripheral blood obtained from pregnant women

Abstract: Concentrations of tissue plasminogen activator (t-PA) and plasminogen activator inhibitor (PAI) were measured in blood obtained from pregnant women to elucidate the fluctuations in the fibrinolytic system which occur during the course of pregnancy. The t-PA activity was measured with a modified bioimmunoassay using anti-t-PA monoclonal antibody (SP-322) against a single chain of recombinant t-PA. The t-PA antigen was measured by ELISA using the same antibody. PAI activity was determined with a competitive inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 5 publications
2
5
1
2
Order By: Relevance
“…t-PA activity decreased during pregnancy as previously described (24). This is partly an effect of the increased production of PAI-1 and PAI-2 in the placenta and the endothelium, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…t-PA activity decreased during pregnancy as previously described (24). This is partly an effect of the increased production of PAI-1 and PAI-2 in the placenta and the endothelium, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast to our obtained data, in earlier published studies, the decrease of t-PA activity in blood plasma during pregnancy was determined [70] and later publications report about the moderate increase of this parameter in pregnant women without any marked pathologies [76,77]. It should be noted that the decrease of t-PA level and activity is connected with an increased risk of thrombosis [78], as well as with intrauterine growth retardation and preeclampsia [79].…”
Section: Partcontrasting
confidence: 95%
“…These statements are based on the fact-finding of prolongation of clot lysis time of fibrin that was collected from blood plasma [67,68], the decrease of t-PA concentration, as well as on the increase of PAI-1 and PAI-2 levels [61,69,70]. Some authors presuppose that the observed changes earlier viewed activators and inhibitors do not influence the general fibrinolytic activity of blood [71,72].…”
Section: Partmentioning
confidence: 99%
“…Plasminogen levels, tissue plasminogen activator (t-PA), and urokinase-type plasminogen activator (u-PA) antigen increase throughout the pregnancy, 9,52,72,[74][75][76][77][78] whereas t-PA activity decreases remarkably. 74,78 There occurs a rise in levels of both plasminogen inhibitors (PAI-1, which increases up to four times the nonpregnant values, 52,60,[75][76][77]79 and PAI-2, which is placenta-derived, increases five times until delivery, compared with the I trimester values). 60,75,77,79 The fast plasmin inhibitor α 2 -antiplasmin is unchanged during pregnancy.…”
Section: Hemostatic Changes During Normal Pregnancy Molecular Changesmentioning
confidence: 99%